Bronze sodium tungsten precipitation synthesis and lithium intercalation - Martins, Tiago A.; Gonçalves, Roger; Cabral, L. [UNESP]; Machado, Thales Rafael; da Silva Paiva, Robert; Roca, Roman Alvarez; Pereira, Ernesto Chaves; San-Miguel, Miguel A.; da Silva, E. Z.; Longo, E. (Springer Nature, 2024)
Hexagonal sodium tungsten bronze (h-NaxWO3+x/2·yH2O) nanorods were obtained by simple acid precipitation in 16 min at 97 °C, evidencing the saving of time and energy. The W-OH2 modes were observed in Raman and Fourier transform infrared (FTIR) spectra to confirm the presence of structural water. The h-NaxWO3+x/2·yH2O was subjected to heat treatment at 300 °C to analyze the effects of heating on the material. X-ray photoelectron spectroscopy (XPS) and diffuse reflectance ultraviolet-visible absorption spectra (UV-vis) indicated the occurrence of diffusion on the surface-bulk of Na+ ions, and the band gap changed from 2.7 eV to 2.4 eV with heating. Electrochromic devices based on h-NaxWO3+x/2·yH2O were constructed. The sample without heat treatment and with structural water loss presented the electrochromic efficiency of 127.5 cm2/C and 561.8 cm2/C, respectively, evidencing the creation of vacancies for the intercalation of lithium ions from heat treatment. Also, density functional theory calculations were performed to study the lithium diffusion process in the interstitial Na-WO6 channels of sodium tungsten bronze. Graphical abstract: (Figure presented.).
Keywords: Electrochromism; Lithium intercalation; Precipitation synthesis; Sodium tungsten bronze